2017
DOI: 10.1002/pc.24377
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing viscoelastic properties of carbon fiber/epoxy composites using vector fitting method

Abstract: In this work, mechanical properties of a T800 carbon fiber/modified epoxy composite material were researched by using a dynamic mechanical analyzer (DMA) operated under flexural mode. The dynamic mechanical behavior was investigated by DMA at a fixed frequency of 1 Hz. Because mechanical properties of the material were influenced by both time and temperature, its viscoelastic modulus was also considered and accomplished by conducting DMA multiple‐frequency dynamic mechanical experiments. Based on the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…The curves represent the translation results of the curves. Comparing them with the research of Li et al, [17] it can be found that the results of automatic shift and manual shift are consistent.…”
Section: Automatic Shiftsupporting
confidence: 78%
See 1 more Smart Citation
“…The curves represent the translation results of the curves. Comparing them with the research of Li et al, [17] it can be found that the results of automatic shift and manual shift are consistent.…”
Section: Automatic Shiftsupporting
confidence: 78%
“…Two examples with different DMA test method are used. The first is the transverse unidirectional CFRP with the frequency sweep/temperature step method, which can be found in the research of Li et al [ 17 ] The second is the epoxy resin with the frequency sweep/continuous heating‐up method, which is carried out by us. Under the same heating rate and temperature range, the test time of the continuous heating‐up method is less than that of the temperature step method.…”
Section: Methodsmentioning
confidence: 99%